PENGARUH LINGKUNGAN SEKOLAH TERHADAP PEMBENTUKAN AQIDAH AKHLAK PADA ANAK USIA DINI - Ines Indriyani; Taukhid Mubarok (CV. ADIBA ASIHA AMIRA, 2024)
Research has been conducted regarding the strategies of Aqidah Akhlak teachers in instilling character in students at MI A-lmujahidin Kluwut. This research is qualitative research using a descriptive qualitative approach. This research only attempts to reveal or describe the information contained in MI Al-Mujahidin Kluwut. Researchers act as key instruments. The origin of the data used means secondary and primary data sources. The approaches used are: a) pedagogical approach, b) psychological approach, and c) social approach. The results obtained include: objective requirements regarding student character at MI Al-Mujahidin Kluwut, in general students have good character. The characteristics that can be observed shown by students in the MI Al- Mujahidin Kluwut environment can be summarized as; Students tend to be obedient, polite towards all teachers and fellow students, disciplined, truly peaceful and always maintain harmony and closeness towards each other. b) There are several supporting and inhibiting factors for teachers of moral beliefs in instilling character in students at MI Al-Mujahidin Kluwut, and c) teachers deliver guidance through lectures (at school and at home), it is recommended/required to read a lot of related things with religion (which is related to character building for students who have problems and are given direction so that they don't repeat the mistakes they have made, students who have problems are handed over to the BK teacher (BP teacher) to be given guidance